2018
DOI: 10.1016/j.cels.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Universal Alternative Splicing of Noncoding Exons

Abstract: The human transcriptome is so large, diverse, and dynamic that, even after a decade of investigation by RNA sequencing (RNA-seq), we have yet to resolve its true dimensions. RNA-seq suffers from an expression-dependent bias that impedes characterization of low-abundance transcripts. We performed targeted single-molecule and short-read RNA-seq to survey the transcriptional landscape of a single human chromosome (Hsa21) at unprecedented resolution. Our analysis reaches the lower limits of the transcriptome, iden… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
95
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 123 publications
(102 citation statements)
references
References 53 publications
6
95
1
Order By: Relevance
“…Indeed, recent studies have indicated that human transcriptome annotations are far from complete, particularly in relation to long noncoding RNAs (lncRNAs) 11,12 . lncRNAs are a diverse class of gene products that qualitatively constitute the major portion of the mammalian transcriptome, but which are still poorly catalogued and characterized 13 . The number of annotated lncRNAs has grown enormously in recent years, with almost 10,000 new lncRNA loci being added to GENCODE since 2009 11 , and many more likely to exist [14][15][16][17] . While only a small subset of annotated lncRNAs have been functionally characterized (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, recent studies have indicated that human transcriptome annotations are far from complete, particularly in relation to long noncoding RNAs (lncRNAs) 11,12 . lncRNAs are a diverse class of gene products that qualitatively constitute the major portion of the mammalian transcriptome, but which are still poorly catalogued and characterized 13 . The number of annotated lncRNAs has grown enormously in recent years, with almost 10,000 new lncRNA loci being added to GENCODE since 2009 11 , and many more likely to exist [14][15][16][17] . While only a small subset of annotated lncRNAs have been functionally characterized (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…RNA CaptureSeq works by targeting specific genomic regions of interest for capture using oligonucleotide probes as baits, providing enhanced sequencing coverage of those regions 15,22,28 . RNA CaptureSeq has facilitated the identification of novel transcript isoforms within even well-studied loci such as TP53 15 , has provided the first genome-wide map of human splicing branchpoints 29 , and has proven particularly useful for the detection and quantification of lncRNAs and their many isoforms 14,22,30,31 . The increased sensitivity and resolution of RNA CaptureSeq make it a logical choice for the profiling of unannotated transcripts arising from non-coding GWAS haplotype blocks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such approaches have been adapted for targeted sequencing of long genomic fragments (>2kb) or full-length cDNA molecules [19][20][21][22][23][24] . In two notable studies described recently, complex pools of biotinylated oligos were used to enrich for and sequence thousands of protein-coding and lncRNA targets, leading to considerable gains in isoform detection and new insights about the nature of transcriptomic complexity 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, deep RNA analysis shows that the human gene complement is far from being fully characterised 7 . A recent high resolution study of the transcriptional output from human chromosome 21 RNA identified over 2000 unannotated isoforms of protein‐coding mRNAs, including almost 300 previously unknown protein‐coding exons 8 . Therefore, given the incomplete characterisation of human gene structure, it is clear that WES is intrinsically inadequate and biased towards the currently incompletely known catalogue of protein‐coding exons.…”
mentioning
confidence: 99%